Pengaruh Suhu danWaktu Distilasi Cairan Pulpa Hasil Samping Fermentasi Biji Kakao Terhadap Karakteristik Distilat Cuka Fermentasi - GandaPutra, Gusti Putu; Wartini, NiMade; Ina, Putu Timur (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 2 (2015), 2015)
The purpose of this study were: 1) to study the effect of temperature and time ofdistillation process of the watery sweatings byproduct of cocoa beans fermentation tor thecharacteristics of vinegar distillate; 2) determine the best distillation process condition whichcan produce of vinegar distillate corresponding their characteristics. This research wasconducted in two stages; the first stage is the evaporation of alcohol by distillation attemperature variations of 90oC and 100oC; and time of 15, 30, 45, and 60 minutes. Thesecond stage is the distillation process using factorial RBD with 2 factors, the first factor istemperature, consists of 90oC and 100oC, and the second factor is the time, consisting of 30,60, 90, 120, and 150 minutes. Each combination of treatments performed in 3 groups inorder to obtain of 24 and 30 experimental units in stage I and II. Observations made include:yield (%, v/v), alcohol content (%), acetic acid content (%), pH, and total soluble solid. Theresults showed that: 1) the first stage of the study, it was determined that the best conditionsof distillation process for evaporation of alcohol is the temperature of 90oC and time of 15minutes; 2) in the second stage of the study, treatment temperature and time of distillationaffect the yield, the alcohol content, and total soluble solid, but has no effect on acetic acidand pH levels of vinegar distillate was produced, and 3) the best conditions of distillationprocess to produce the vinegar distillate is the temperature of 100oC, the time of 150minutes.
Keywords: cacao, watery sweatings, distillation, vinegar